An IoT Platform for the Management of Fruit Fly Electric Traps - Tran, Vy-Khang; Tran, Quoc-Duy; Nguyen, Chi-Ngon; Nguyen, Van-Khanh (Journal of Science and Technology, 2026)
The Oriental fruit fly is a major agricultural pest that directly impacts crop yield and quality. However, current monitoring methods are still largely manual, lacking automation and continuity. This study proposes a remote monitoring platform that integrates automated electronic traps, Long Range (LoRa) communication, and an intuitive web interface. The system comprises sensor stations that transmit real-time data to a customized remote server via the internet, where the data are processed, stored using a JSON file-based NoSQL structure, and visualized through a web-based dashboard. The server supports concurrent monitoring of multiple stations, historical data access, and real-time device status tracking. Secure data transmission is ensured through Hypertext Transfer Protocol Secure (HTTPS) / Transport Layer Security (TLS) protocols integrated with Cloudflare services. Field experiments at two test stations achieved detection accuracies of 86.76% and 93.50%, respectively. The platform demonstrates strong potential for practical deployment in automated and large-scale pest management. Future enhancements will focus on integrating early warning capabilities, advanced data analytics, and scalable architecture to better support smart agriculture applications.